Analysis of the black‐chinned tilapia Sarotherodon melanotheron heudelotii reproducing under a wide range of salinities: from RNA‐seq to candidate genes. (25th July 2013) - Avarre, J.‐C.; Dugué, R.; Alonso, P.; Diombokho, A.; Joffrois, C.; Faivre, N.; Cochet, C.; Durand, J.‐D.
Abstract The black‐chinned tilapia Sarotherodon melanotheron heudelotii is an ecologically appealing model as it shows exceptional adaptive capacities, especially with regard to salinity. In spite of this, this species is devoid of genomic resources, which impedes the understanding of such remarkable features. De novo assembly of transcript sequences produced by next‐generation sequencing technologies offers a rapid approach to obtain expressed gene sequences for non‐model organisms. It also facilitates the development of quantitative real‐time PCR (qPCR) assays for analysing gene expression under different environmental conditions. Nevertheless, obtaining accurate and reliable qPCR results from such data requires a number of validations prior to interpretation. The transcriptome of S. melanotheron was sequenced to discover transcripts potentially involved in the plasticity of male reproduction in response to salinity variations. A set of 54 candidate and reference genes was selected through a digital gene expression (DGE) approach, and a de novo qPCR assay using these genes was validated for further detailed expression analyses. A user‐friendly web interface was created for easy handling of the sequence data. This sequence collection represents a major transcriptomic resource for S. melanotheron and will provide a useful tool for functional genomics and genetics studies.